2022
DOI: 10.3390/toxins14020139
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cross-Sectional Muscle Growth Six Months after Botulinum Toxin Type-A Injection in Children with Spastic Cerebral Palsy

Nathalie De Beukelaer,
Guido Weide,
Ester Huyghe
et al.

Abstract: Botulinum Neurotoxin type-A (BoNT-A) injections are widely used as first-line spasticity treatment in spastic cerebral palsy (SCP). Despite improved clinical outcomes, concerns regarding harmful effects on muscle morphology have been raised. Yet, the risk of initiating BoNT-A to reduce muscle growth remains unclear. This study investigated medial gastrocnemius (MG) morphological muscle growth in children with SCP (n = 26, median age of 5.2 years (3.5)), assessed by 3D-freehand ultrasound prior to and six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 59 publications
(96 reference statements)
8
32
0
Order By: Relevance
“…Muscle growth rates, calculated over the period between the two assessments, were not significantly different from the control group. Several studies have reported similar rates of muscle atrophy after BoNT-A injections [ 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Muscle growth rates, calculated over the period between the two assessments, were not significantly different from the control group. Several studies have reported similar rates of muscle atrophy after BoNT-A injections [ 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by De Beukelaer et al was the first to quantify the BoNT-A effect on muscle morphology in an intervention group compared to a control group of children who did not receive BoNT-A treatment. They showed a reduction in anatomical cross-sectional area six months after the first BoNT-A injection, which was not observed in the control group of children, who remained BoNT-A naive during this period [ 26 ]. They did not find any significant between group differences in muscle volume following BoNT-A.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations